FRI0159 Longstanding active giant cell arteritis (gca) treated with infliximab: report of four casesinfliximab. (1st June 2001) - Cantini, F; Niccoli, L; Salvarani, C; Boiardi, L; Olivieri, I; Padula, A
Abstract : Background: TNF-alpha was demonstrated in up to 60% of the cells in all areas of inflamed arteries of patients with GCA, suggesting a primary role in the inflammatory process. Infliximab, a chimeric monoclonal anti-TNF-alpha, demonstrated remarkable efficacy and safety in the treatment of several rheumatic conditions associated with a chronic inflammatory response. Objectives: To date, no data are available on the therapeutic employment of infliximab in patients with GCA. The aim of this study was to evaluate the efficacy of infliximab infusions in longstanding, still requiring corticosteroids (CS) GCA. Methods: Four patients (3F, 1M; median age:75 ys.) with longstanding (median disease duration: 4 ys.), biopsy proven, active GCA, still requiring CS and whose disease course hab been complicated by serious CS-related adverse events, were scheduled to receive 3 infusions of infliximab (3 mg/Kg) at weeks 0, 2 and 6. If a clinical and humoral remission was obtained, CS were withdrawn after the 2nd infusion. Results: Three patients had a complete remission of clinical signs/symptoms and normalisation of ESR and CRP after the 2nd infusion. The remission persisted after the 3rd infusion and over the follow-up (7, 6 and 6 months, respectively). The fourth patient did not respond to therapy and withdrew from the study after the 2nd infusion. Infliximab was well tolerated without any side-effects. Conclusion: Our encouraging results suggest that TNF-alpha blockade may represent a valid alternative therapeutic approach to longstanding GCA, still requiring CS and complicated by severe adverse events. The small number of patients and the open study design do not allow conclusive considerations.